Kennedy disease with difficulty in differential diagnosis: A case report. Issue 19 (May 2017) - Chen, Yating; Luo, Peng; Li, Zhongli; Hu, Hengping; Wu, Duobin; Xu, Tingting; Wang, Xingzuo; Xie, Haiting
Abstract: Rationale: Kennedy disease (KD) is also known as spinal bulbar muscular dystrophy. As KD has similar symptoms with most neuromuscular diseases, so it is difficult to make a rapid diagnosis clinically. Patient concerns: We report a case of a 43-year-old male with progressive limb proximal weakness without family history. Physical examination showed gynecomastia, erectile dysfunction, bilateral tendon reflex and quadriceps weakness, and tongue muscle atrophy. Diagnoses: Laboratory examination found increased creatine kinase, impaired glucose tolerance, and abnormal lactic acid values. There was no mutation or copy number variant in SMN1 gene and related mitochondrion genes tested, even with the use of multiplex ligation probe- dependent amplification technique. Diagnosis was confirmed with genetic analysis which displayed trinucleotide CAG (glutamine)- repeat expansion in the androgen-receptor gene. Interventions and Outcomes: The patient achieved good prognosis with symptomatic treatment after diagnosis. Lessons: To diagnose KD, clinicians should pay more attention to differentiate KD and myasthenia gravis, mitochondrial myopathy, and amyotrophic lateral sclerosis. Gene analysis was the key in detecting this rare confusing disease in the patient.